The Effect Of Training And Work Motivation On Work Productivity In Citra Printing And Digital Printing In Pangkep Regency - Muh. Ikram; Ahmad, Ahmad; Ismail Rasulong (CV. AFDIFAL MAJU BERKAH, 2024)
This research is quantitative research. The aim of this research is to determine the effect of training and work motivation on employee work productivity at Image Printing and Digital Printing in Pangkep Regency. The sampling method used in this research is a saturated sample or taking the entire population with 35 sample respondents. The data in this research was obtained from the results of distributing questionnaires that had been distributed. The analytical method used is descriptive analysis method and multiple linear regression analysis using the IBM SPSS version 22 for Windows application. The results of this research show that partially training and work motivation have a positive and significant effect on employee work productivity at Citra Printing and Digital Printing in Pangkep Regency.